PERANCANGAN DAN IMPLEMENTASI JARINGAN WIRELESS POINT TO POINT UNTUK WARGA DESA TRIMODADI KEC ABUNG SELATAN - Adi Wibowo; Ristyo (Sienna, 2020)
A good and smooth internet access is very beneficial for all parties especially during Covid-19 outbreak which afflicted around the world. It can helps to implement healthy protocol and to do activities from the house including working and studying. However, there are several places which have not been reached by the internet which therefore it needs internet networks. Point to point networks will be built in this research in order to give internet network services for the societies in Trimodadi, Abung Selatan District which has not been reached by optic fiber. This network was built by Metal Microtic 5 SHPN and 5.8 Ghz 30 dBi Grid Anthen as the point to point transmitter in location A which located in central Kotabumi meanwhile in location B which is located in Trimodadi, Abung Selatan District used Metal Microtic 5 SHPN.